Optimasi Komposisi Pupuk Tanaman Jagung Menggunakan Algoritme Genetika - Arik Khusnul Khotimah; Nurul Hidayat; Moch. Cholil Mahfud (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
At this time, produce of corn can not be fill the needs in this country. This caused productivity of corn decreased in a few years. The way to solve that problem is increase productivity of corn. Some of the way to increase productivity of corn is balance fertilizer. For fertilization, the main problem of farmers is the high fertilizer price mainly type N, P, and K fertilizer. Therefore, it need some data processing for measuring the composition of fertilizer with price of fertilizer for the best result. The result of data processing can be used for farmer to measure the composition of fertilizer which fit with the best price recommendation. This research used genetic algorithm. This algorithm used to optimize composition of fertilizer. The solution of this algorithm use representation chromosome real code, crossover process use one cut point, mutation process use reciprocal exchange mutation, and selection process use binary tournament selection. Based on testing, the optimal result is on size of population as much 9, 12 generation, crossover rate composition and mutation 0,7 and 0,3, 0,4 and 0,6, 0,1 and 0,9, 0 and 1 with highest fitness is 0,8403.